Android Application for the Plan and Elevation Topic in Form Five Mathematics - Hamzah, Norhasyimah; Muhammad Hamzah A Rahman; Siti Nur Kamariah Rubani; Arihasnida Ariffin; Normah Zakaria (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: An android application for the ‘Plan and Elevation’ topic was developed in this study as it was found that there were issues in education regarding students’ unsatisfactory academic achievement in the topic’s teaching and learning (T&L) process. Students’ difficulty in mastering geometry learning was found to be due to weaknesses in their spatial-visual skills. This study aims to (i) help teachers by providing a teaching aid that can be used in the T&L process, and (ii) allow students to learn at any time on their own and not be limited to class-learning. The development of this android application also helps users to learn how to solve problems related to the topic of Plan and Elevation. In this study, an android application was developed using the ASSURE design model. The model consisted of six phases namely student analysis; statement of objectives; selection of methods, media, and materials; use of media and materials; involvement of students in learning; and product evaluation. Adobe Flash Professional CS6 was used as the android application’s development platform. The android application has four sections: "Introduction", "Topics", "Learning Videos" and "Mind Questions". The research instrument used is a questionnaire form aimed at confirming the functionality of this application. Developers collected research data from lecturers of related expertise from the Faculty of Technical and Vocational Education. In conclusion, the use of the android application for learning the Plan and Elevation topic will help improve students’ mathematic achievements, especially those which do not involve computation. This will potentially impose positive impact on the T&L process. Keywords: Android application, Development, Mathematics, Plan and elevation